Rasch Model Analysis for IoT-based PJBL Hybrid Learning Design in MBKM Curriculum - Eko Risdianto; Hamed Barjesteh; Mageswaran Sanmugam; M. Abdul Jamal (CV Media Inti Teknologi, 2025)
Background of study: Even though the use of Project-Based Learning (PjBL) and the Internet of Things (IoT) in education is still growing, the integration of these two technologies in high-level education is still being explored, particularly in the use of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum and the Indikator Kinerja Utama (IKU). This kesenjangan highlights the need for innovative teaching methods that integrate pedagogy and technology to meet the challenges of the digital age.Aims: The purpose of this study is to analyze the need for developing collaborative hibrida learning designs that integrate PjBL and IoT technology in order to execute MBKM curricula and reach IKU pendidikan tinggi.Methods: This study employs a survey methodology in which data is collected by a survey consisting of eighteen questions posed to university professors. Model Rasch with Winstep lunak perangkat is used for data analysis to assess the validity and reliability of research instruments.Result: Results indicate a strong demand for a hybrid learning system that effectively combines PjBL with IoT to support collaborative and interactive learning. The instrument reliability achieved a Cronbach Alpha of 0.95, indicating excellent reliability, while the Person Reliability and Item Reliability were measured at 0.90 and 0.46, respectively. The findings suggest that all questionnaire items were fit for assessing the critical thinking capabilities of students across different institutions.Conclusion: These results highlight the necessity of developing hybrid learning models to address educational challenges in the digital era, ensuring curriculum alignment and facilitating the achievement of MBKM goals. This study contributes to advancing higher education by providing actionable insights into learning design development that integrates cutting-edge technologies.